Return to Work After Release From Prison - Candura, Stefano Massimo; Madeo, Domenico; Negri, Claudia; Scafa, Fabrizio (La Medicina del Lavoro, 2024)
Work preservation is crucial for the reintegration of ex-prisoners and the prevention of recidivism. We describe the application of an interdisciplinary diagnostic protocol (occupational health visit, psychiatric interview, psychological counselling and testing) in the case of a dairy industry worker (female, 45-year-old), released on half-freedom after approximately a year of detention in prison for attempted murder. This crime can seriously hamper job resumption. The evaluation revealed a slightly depressed mood (consistent with recent life events), in the absence of major psychiatric disorders or other disturbances that could compromise working abilities or represent a danger for the coworkers. The patient was, therefore, judged able to resume her job. At six months follow-up, she had fully served her sentence and had returned to her previous job, with good relations with her colleagues. However, she encountered hostility from her employer, which induced her to find a new job as a secretary. Her mental health status was improved. The interdisciplinary approach described here may allow ex-prisoners to return to work by helping the company physician to formulate the judgement of job fitness, offering at the same time suggestions for a rational occupational reintegration.